2019
DOI: 10.1144/jgs2019-070
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Late Pleistocene loess particles by katabatic winds during the lowstands of the English Channel

Abstract: Studies of the submerged Pleistocene conglomerate cored and dredged in the English Channel show that it resulted from the cementation of stony beaches under a loess blanket. Although the loess cover was later washed out by younger transgressions, the northern limit of the conglomerate corresponds to the original offshore extension of the loess deposits. Compilation of offshore and onshore altitudes of the limits of these deposits shows that loess was deposited by low-level wind fields never thicker than 200 m.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…By contrast, loess deposited on the north-facing slopes would be equivalent to the deposits of northern Brittany and those of Portelet would represent leeward deposits associated with the katabatic winds. • The absence of Neanderthals during the thicker loess sedimentation (Scott et al, 2014) confirms the previous observations made onshore in Brittany (Lefort et al, 2019b) since it is during these episodes that katabatic winds were stronger and Neanderthals were absent (Fig. 5).…”
Section: Contribution Of Jersey and Guernsey To The Environment Of Neanderthalssupporting
confidence: 87%
See 4 more Smart Citations
“…By contrast, loess deposited on the north-facing slopes would be equivalent to the deposits of northern Brittany and those of Portelet would represent leeward deposits associated with the katabatic winds. • The absence of Neanderthals during the thicker loess sedimentation (Scott et al, 2014) confirms the previous observations made onshore in Brittany (Lefort et al, 2019b) since it is during these episodes that katabatic winds were stronger and Neanderthals were absent (Fig. 5).…”
Section: Contribution Of Jersey and Guernsey To The Environment Of Neanderthalssupporting
confidence: 87%
“…This approach is an entirely new one when compared to the former models. In the present review, the physical parameters used in the study by Lefort et al (2019b) will only be summarized; details of this study can be found in the full article.…”
Section: Regional Background and Previous Researchmentioning
confidence: 99%
See 3 more Smart Citations